2016
DOI: 10.1093/ecco-jcc/jjw203
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Short- and Medium-term Efficacy of Biosimilar Infliximab Therapy. Do Trough Levels and Antidrug Antibody Levels or Clinical And Biochemical Markers Play the More Important Role?

Abstract: In UC, early TLs were predictive for short- and medium-term clinical efficacy, whereas in CD, Week 2 TLs were associated only with short-term clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
1
34
1
Order By: Relevance
“…Data on predictors on long-term are missing. However, the study by Gonczi et al revealed that week 2 trough levels of CT-P13 were predictive for short- and medium-term clinical efficacy in UC and were associated only with short-term clinical outcomes in CD [22]. In our study, we were not able to show any of the examined parameters to predict the outcome of CT-P13 therapy at week 54 neither in CD nor in UC.…”
Section: Discussioncontrasting
confidence: 96%
“…Data on predictors on long-term are missing. However, the study by Gonczi et al revealed that week 2 trough levels of CT-P13 were predictive for short- and medium-term clinical efficacy in UC and were associated only with short-term clinical outcomes in CD [22]. In our study, we were not able to show any of the examined parameters to predict the outcome of CT-P13 therapy at week 54 neither in CD nor in UC.…”
Section: Discussioncontrasting
confidence: 96%
“…97 Although well-designed large prospective studies are lacking, there are preliminary data mainly from retrospective studies that demonstrate that proactive TDM is associated with better therapeutic outcomes compared with empiric dose optimization and/or reactive TDM. 38,39,103,104,128 Furthermore, numerous retrospective studies 23,24,26,29,[31][32][33]67,73,74,[77][78][79]129,130 and some post hoc analyses of RCTs [47][48][49]71,76,94,131,132 have shown that higher biologic drug concentrations are associated with favorable short-term and long-term therapeutic outcomes in IBD (Supplementary Table 1, Tables 1 and 2). There do appear to be certain clinical scenarios that proactive TDM of anti-TNF therapy can efficiently guide therapeutic decisions, such as treatment de-escalation, 133 the application of optimized monotherapy instead of combo therapy with immunomodulator, 82 restarting therapy after a long drug holiday, 27 and treatment cessation on deep remission.…”
Section: Discussionmentioning
confidence: 99%
“…CD patients exposed to infliximab over 12 months prior to initiating CT-P13 therapy demonstrated significantly reduced clinical response and remission up to week 54 (p < 0.005) and higher ADA levels in early treatment (week 2, p < 0.001). Previously treated UC patients demonstrated significantly reduced clinical remission (p ≤ 0.03) and ADA development up to week 6 (p < 0.02) versus infliximab-naïve UC patients [74]. No differences were observed at weeks 14 or 30.…”
Section: Impact Of Non-medical Switch On Immunogenicitymentioning
confidence: 87%